CHARF LĀM DALAM CERPEN AʻŪDZU BIKA MINKA KARYA ICHSĀN ʻABDUAL-QUDDŪS (KAJIAN SINTAKSIS) - Yudi Adistiro, Afnan Arummi (Arabic Literature Department, 2017)
This research was conducted to describe the function of